Religion and Pain: Prediction of Pain Dimensions Based on Patience - A Valikhani; F Khormaei (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: Chronic pain as a disabling disorder dose not completely respond to the routine medical treatments. Consequently identification of the risk factors and psychologic-protective factors of pain such as religion and spirituality seems necessary. The aim of this study was to predict the physical, emotional, and cognitive dimensions of pain based on patience.  Material & Methods: It was a correlational structural equation modeling study. A total of 110 patients with cardiovascular diseases were recruited by convenient sampling from the outpatient clinic of Imam Reza in the city of Shiraz. Data was collected by a researcher made patience scale and chronic pain inventory and analyzed by Pearson correlation analysis and structural equation modeling using SPSS-PS (v.16) and Amos 16.0. Results: The results showed that patience is negatively correlated with total pain and its physical, emotional, and cognitive dimensions (p< 0.01). There was a significant negative relationship between the subscales of patience, tolerance and consent with total pain and its triple dimensions (p< 0.05). The subscale of delay was negatively associated with total pain and its physical dimension (p< 0.05). There was no significant relationship between transcendence and persistence with pain and its dimensions. The structural equation modeling (SEM) showed that the patience latent variable has strongly predicted the pain (β= -0.44, p< 0.05). Conclusion: Regarding the findings, it could be concluded that psychological factors especially religious variables play an important role in alleviating pain in cardiovascular diseases. In between, patience as an important variable in the experience of physical, emotional and psychological dimensions of pain could have an important role.